The effect of hemorrhage control adjuncts on outcome in severe pelvic fracture: A multi-institutional study. Issue 1 (July 2019) - Duchesne, Juan; Costantini, Todd W.; Khan, Mansoor; Taub, Ethan; Rhee, Peter; Morse, Bryan; Namias, Nicholas; Schwarz, Alon; Graves, Joanne; Kim, Dennis Y.; Howell, Erin; Sperry, Jason; et al.
Abstract : BACKGROUND: Hemodynamically unstable patients with severe pelvic fracture are a significant challenge to trauma surgeons and have high mortality. Significant variability across institutions in hemorrhage control adjuncts used to quell pelvic bleeding has been demonstrated. However, the effect of these methods on time to definitive bleeding control, type of resuscitation given, and outcomes remains unknown. We sought to elucidate those effects. METHODS: This was a multicenter retrospective review of severe pelvic fracture patients in shock between 2011 and 2016. Shock was defined as systolic blood pressure less than 90 mm Hg, heart rate greater than 120 beats per minute, or base deficit less than −5. Definitive bleeding control was defined as time to surgical control in the operating room or embolization by interventional radiology. Significance level was at p less than 0.05. RESULTS: A total of 279 severe pelvic fracture patients with shock on admission from 12 trauma centers were included. The cohort was primarily male (62%) with median (interquartile range) age of 40 years (28–54 years), Injury Severity Score of 38 (29–50), and Glasgow Coma Scale score of 13 (3–15). Overall mortality was 32%. The most common adjunct used was pelvic binder (50%) followed by no adjunct (30.5%); least common was resuscitative balloon occlusion of the aorta (REBOA) (2.5%). Preperitoneal packing alone and REBOA alone/with other adjunct(s) resulted in the fastest times to operating room/interventional radiology but also had the highest blood utilization and mortality rates. Resuscitative balloon occlusion of the aorta was most often used along with pelvic binder (6 of 13; 46%). CONCLUSION: Marked variation in management of severe pelvic fracture patients in shock indicates the need for a standardized approach to maximize outcomes and minimize transfusion requirements. The use of preperitoneal packing and/or REBOA yielded fastest times to definitive bleeding control. However, REBOA continues to be infrequently used. Future prospective analysis of this combination needs further validation in patients with severe pelvic hemorrhage. LEVEL OF EVIDENCE: Therapeutic study, level IV.